Phylogeography of ‘tropical Daphnia ’ — Diaphanosoma dubium : Refugia, Lineage Divergence, and Historical Colonization Over a Warm and Complex Landscape in East Asia - Ping Liu; Meng Xu; Qi Huang; Henri J. Dumont; Diego Fontaneto; Bo‐Ping Han (Journal of Biogeography, 2026)
Aim East Asia spans temperate to tropical zones, with limited glacial influence and a complex geological history shaped by the Tibetan Plateau. Consequently, species here may show distinct phylogeographic patterns compared with those of Europe and North America. Using the warm‐adapted cladoceran Diaphanosoma dubium as a model, we tested whether it persisted in multiple watershed refugia, especially the Yangtze River Basin, during past climate oscillations, leading to geographically structured lineage divergence. Location East Asia, with a specific focus on watersheds across China. Taxon The cyclically parthenogenetic cladoceran Diaphanosoma dubium (‘tropical Daphnia ’). Methods We applied ecological niche modelling on a global occurrence dataset and population genetics analyses on mitochondrial and nuclear gene datasets from 60 populations. Results High‐fitness areas were identified mainly in the eastern Yellow River Basin plains during the Last Glacial Maximum (LGM). Phylogenetic analysis resolved five deep lineages coalescing in the Late Miocene. Ancestral cold‐adapted lineages dominated the Yellow River Basin in the Late Miocene, later dispersing and permeating southward into the Yangtze River Basin during pre‐Pleistocene cooling. Three deep lineages indicated a large refugium downstream of the Yellow River Basin and west of the Bohai Gulf, and two lineages indicated two cryptic southern refugia. The two most common lineages overlapped widely in China, expanding post‐LGM from the Paleo‐Bohai refugium, showing climate tracking and niche conservatism. Main Conclusion In contrast to our expectation, the Yangtze River Basin acted as a dispersal hub rather than a refugium in middle China. D. dubium exhibited a watershed‐associated latitudinal structure, distinct from Daphnia in Europe. Historical north‐to‐south colonization and strong gene flow mitigated genetic differentiation among watersheds. Life‐history traits drove D. dubium 's successful colonization of tropical China, with geographic range and mountainous landscapes further shaping its continental‐scale distribution and divergence.